Role of protease-activated receptor 2 in regulation of renin synthesis and secretion in mice - Thurner, Lena Ruth; Höcherl, Klaus (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)
It has been reported that the serine protease kallikrein stimulates and that aprotinin, a protease inhibitor, inhibits renal renin secretion. Since direct stimulation of the protease-activated receptor (PAR) 2 increases renin secretion in isolated perfused mouse kidneys, we hypothesized that activation of PAR2 receptors by serine proteases could be involved in the synthesis and secretion of renin in vivo. We therefore determined the response of plasma renin concentration (PRC) to acute intraperitoneal administration of the PAR2 agonist SLIGRL, isoproterenol, hydralazine, furosemide, losartan, or lipopolysaccharide in conscious wild-type (WT) and Par2-deficient mice. Basal PRC was not different in Par2-deficient mice compared with WT mice. All six acute treatments caused significant increases of PRC in both WT and Par2-deficient mice. The response was significantly lower only in endotoxin-treated Par2-deficient mice. Chronic treatment with losartan, low salt intake, the combination of both, or furosemide caused an increase of PRC and renin mRNA in WT mice, whereas a high salt intake caused a decrease. Alterations in PRC and renal renin mRNA expression were not different between WT and Par2 -/- mice in response to chronic treatments. Par2-deficiency did not alter furosemide-induced diuresis and natriuresis. Systolic blood pressure responses to chronic treatments were not different between WT and Par2 -/- mice. In conclusion, deficiency of Par2 receptors does not alter renin secretion and renin gene expression modulated by a variety of typical maneuvers. However, activation of Par2 receptors by serine proteases seems to be of importance for renin secretion in the context of inflammation.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Angiotensin; F2RL1; Kidney; Lipopolysaccharide; Renin